Odpowiedzi

2009-10-26T20:27:55+01:00
A) 3 *√7 I 3√7
______ = I ---------
√7 * √7 I 7

2 *³√4*³√4 I 2³√16
________ = I ____________
³√4*³√4*³√4 I 4

e) 5*(√2+√3+√5 ) I 5√2+5√3+5√5
__________ =I ----------------------------------------
√2+√3+√5*(√2+√3+√5 ) I10

Powinno być good
Pozdro
2009-10-26T20:32:54+01:00
A) 3 3 * √7 3√7
____= _________ = _______
√7 √7 * √7 7

b) 6 6 (√3 + 2) 6 (√3+2)
____ = ________________ = ________ = - 6√3 - 12
√3-2 (√3-2) * (√3 + 2) 3-4

c) 4√2 4√2 (√3-√2) 4√6-8
_______ = _______________ = _________ = 4√6-8
√3 + √2 (√3+√2)*(√3-√2) 3-2

d) 2 2∛16 2∛16 2∛16 ∛16
___ = ________ = ________ = _______ = _____
∛4 ∛4*∛16 ∛64 4 2
Najlepsza Odpowiedź!
2009-10-26T21:08:55+01:00
3\√7=3*√7\√7*√7=3√7\7

6\√3-2=6*√3+2\(√3-2)*(√3+2=6√3+2\3-4=-6√3+2

4√2\√3+√2=(4√2)*(√3-√2)\(√3+√2)*(√3-√2)=4√6-8\3-1=4√6-8

5\√2+√3+√5=5(√2-√3-√5)\(√2+√3+√5)(√2-√3-√5)=5√2-5√3-5√5\-6

2\∛4=2\2=1